2021
DOI: 10.11648/j.jcebe.20210502.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rhizobium Inoculation, NPS Fertilizer and Vermicompost on Nodulation and Yield of Soybean (<i>Glycine max</i> (l). Merrill) at Bako, Western Ethiopia

Abstract: In Ethiopia, acidity-related soil fertility problems are the main production constraints, reducing productivity of major crops grown in the country. The experiment was carried out to determine influence of Blended NPS fertilizer, Seed Inoculation with Rhizobium Bacteria and Vermicompost (VC) application on soybean nodulation and yield of soybean. Factorial combinations of Rhizobium (uninoculated, inoculated), three VC levels (0, 1 and 2 t ha -1 ) and three NPS levels (50%, 75% and 100% of 100 kg NPS ha -1 ) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…The results of this study resulted in a lower number of pods when compared to the results of a study by Debela et al, (2021) which was conducted in the country of Ethiopia, the results of the research are that the maximum number of pods per plant (87.6) was produced at the combination of highest rates of the two fertilizers (100 kg NPS ha-1, 2 tons vermicompost ha-1) with inoculation whereas the minimum number of pods per plant (51.53) was recorded from plants supplied with combined 50kg NPS ha-1 with 0 ton vermicompost ha-1 without inoculation. This indicates that the synergistic effect of the mineral fertilizers and mineralization of organic manures and bio-fertilizer throughout growing period did not put the plants nutrient stress at any stage resulting in enhancing number of pods per plants.…”
Section: Pod Amount Per Plant (Fruit)contrasting
confidence: 65%
“…The results of this study resulted in a lower number of pods when compared to the results of a study by Debela et al, (2021) which was conducted in the country of Ethiopia, the results of the research are that the maximum number of pods per plant (87.6) was produced at the combination of highest rates of the two fertilizers (100 kg NPS ha-1, 2 tons vermicompost ha-1) with inoculation whereas the minimum number of pods per plant (51.53) was recorded from plants supplied with combined 50kg NPS ha-1 with 0 ton vermicompost ha-1 without inoculation. This indicates that the synergistic effect of the mineral fertilizers and mineralization of organic manures and bio-fertilizer throughout growing period did not put the plants nutrient stress at any stage resulting in enhancing number of pods per plants.…”
Section: Pod Amount Per Plant (Fruit)contrasting
confidence: 65%
“…Farmers can use rhizobial inoculation to maximize grain legume yields with suitable and appropriate rhizobia where a low population of local rhizobial strains predominates. Debela et al (2021) reported increased plant growth and nodulation efficiency by 80-90% through inoculation with abiotic stress-tolerant cluster bean rhizobial isolates. However, there are two most popular methods for utilizing BNF: the first is improved crop, soil, and water management to maximize BNF potential; the second is Rhizobium inoculation or host genotype selection to ensure increased nitrogen fixation in the plant (Pankievicz et al, 2019).…”
Section: Nitrogen-fixing Bacteriamentioning
confidence: 99%
“…It is considered that more than 50% of crop yield increase from the total number of measures is accounted for by fertilization. Known methods of application: surface and subsurface, solid and local, separate and seedbed (Liang et al, 2014;Debela et al, 2021).…”
Section: Introductionmentioning
confidence: 99%